Practising post‐humanism in geographical research. Issue 4 (2nd July 2019) - Williams, Nina; Patchett, Merle; Lapworth, Andrew; Roberts, Tom; Keating, Thomas
Abstract : Post‐humanist theories shaping contemporary geographic research have unsettled the privileged position of the "human" as a common reference to apprehend social life. This decentring of the human demands that we rethink our expectations of, and approaches to, methodological practice and the traditional distinctions made between the theoretical and the empirical. In this introduction and the following interventions, we explore how a material situatedness and attention to nonhuman agencies within post‐humanist thought complement and extend existing methodological innovations within human geography. We do so with reference to a series of Masters workshops – a somewhat overlooked space of research‐creation – each of which explored the implications of post‐humanism on methodological practice. The introduction concludes with three key tenets that were followed in each of the individual workshops, and which set out an ethos for practising post‐humanism more broadly. Abstract : This themed intervention explores how a material situatedness and attention to nonhuman agencies developed within post‐humanist thought can complement and extend existing methodological innovations within human geography. We do so with reference to a series of Masters workshops – a somewhat overlooked space of research‐creation – each of which attempted to unsettle the privileged position of the "human" in research practice.